Exploratory analysis of an adult client’s interpretative verbal (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
Considering that one of the main behavior therapy purpose is to promote the client’s self-knowledge, the objective of this study was to analyse the verbal responses of an adult client categorized as “interpretative” in the clinical context according to the definitions of a previous study. The method consisted of the analysis and classification of 14 therapeutic sessions. The results showed the occurrence of the following categories in the client’s verbal repertoire: Information, Investigation, Interpretation and Consequencing. It was also found that: a) interpretations occurred in 74,88% of the client’s verbal episodes; b) the client interpreted with the function of explaining something in 78,00% of the interpretations and c) the client focused her own behavior in 73,20% of the interpretations. Such results seem to confirm the hypothesis of that the therapeutical setting is an environment in which the emission of interpretations is favored, thus contributing to the client´s self-knowledge.